Locked in and coming out a textual analysis of Filipino boys' love during the Covid-19 pandemic - Manangan, John Carlo C.; Sanchez, Louie Jon A (Quezon City College of Mass Communication, University of the Philippines, 2023)
In 2020, Filipino audiences saw the rise of a new genre of Filipino-produced shows characterized by narratives of romance between two young boys — Filipino Boys' Love. Its popularity came during a time of unprecedented circumstances brought on by the COVID-19 pandemic that has imposed new restrictions and health protocols in the country, including new protocols in media productions.

This raises important questions about how queer individuals are represented in these series. Guided by the tenets of Queer Theory and Stuart Hall's Theory of Representation, this study analyzed three Filipino Boys' Love series produced in 2020, namely Gameboys (2020), Hello Stranger (2020), and Ben X Jim (2020).

It is undeniable that Boys' Love marks a significant moment for queer visibility in the country. The genre brings welcome developments in gay representation, characterized by positive themes and resolutions, more accepting coming out narratives, and a lesser emphasis on sexual activities. However, it was overwhelmingly apparent that characters with heteronormatively masculine characteristics are privileged in Filipino Boys' Love, and that there is a significant lack of representation of other LGBTQ+ individuals.
Taong 2020 nang sumikat ang isang genre ng mga palabas na gawang Pilipino tungkol sa mga kuwento ng pag-iibigan ng dalawang batang lalaki — ang Filipino Boys' Love. Sumikat ang genre na ito sa kalagitnaan ng pandemyang COVID-19 na nag-udyok ng mga bagong health protocols sa bansa, kasama na ang mga bagong protocols sa mga produksyon sa midya.

Dahil dito, mahalagang pag-aralan ang representasyon ng mga LGBTQ+ sa Boys' Love. Sa gabay ng Queer Theory ni Judith Butler at Theory of Representation ni Stuart Hall, nagsuri ang pag-aaral na ito ng tatlong Filipino Boys' Love series na ginawa noong 2020, ang Gameboys (2020), Hello Stranger (2020), at Ben X Jim (2020).
Hindi maitatanggi na mahalagang sandali ang pag-usbong ng Boys' Love para sa representation ng mga LGBTQIA+ sa bansa. Nagdadala ito ng positibong pagbabago sa kanilang representasyon sa pamamagitan ng positibong mga tema at resolusvon, mas positibong mga kuwento ng pagladlad, at mas kaunting diin sa mga seksuwal na aktibidad. Gayunpaman, maliwanag din na mas binibigyang-pansin an mga karakter na tila heterosekswal ang katangian, at may malaking kakulangan sa representasyon ibang miyembro ng komunidad ng LGBTQIA +.
Vita.
Thesis
Includes bibliographical references (pages 75-79) and appendices (pages 80-92).
Keywords: Gay people in motion pictures; COVID-19 Pandemic, 2020—-Influence.; Mass media and gay people